2013
DOI: 10.1111/j.1435-5957.2012.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

The regional distribution of unemployment: What do micro‐data tell us?

Abstract: Regional disparities in unemployment rates are large and persistent. The literature provides evidence of their magnitude as well as of the role of certain factors in explaining the unemployment gap between regions. Most of these studies, however, adopt an aggregate approach and so do not account for the individual characteristics in each region. This paper, by drawing on micro‐data from the Spanish wave of the Labour Force Survey, seeks to remedy this shortcoming. An appropriate decomposition of the regional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Other studies have shown how sheltered regions are much more vulnerable to a prolonged economic crisis (Fratesi & Rodríguez‐Pose, ), and that differences in the strength of labour market institutions (Ríos, ) or in human capital endowment (Lo Cascio, Mazzola, & Epifanio, ) contribute to explaining increasing disparities. The Spanish labour market is characterized by wide and persistent employment growth disparities (López‐Bazo & Motellon, ) which blow out of proportion during periods of economic expansion and shrink during periods of recession (Bande & Martín‐Román, ; Sala & Trivín, ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Other studies have shown how sheltered regions are much more vulnerable to a prolonged economic crisis (Fratesi & Rodríguez‐Pose, ), and that differences in the strength of labour market institutions (Ríos, ) or in human capital endowment (Lo Cascio, Mazzola, & Epifanio, ) contribute to explaining increasing disparities. The Spanish labour market is characterized by wide and persistent employment growth disparities (López‐Bazo & Motellon, ) which blow out of proportion during periods of economic expansion and shrink during periods of recession (Bande & Martín‐Román, ; Sala & Trivín, ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Another part of empirical research is focused on regional differences in the unemployment level, see e.g. (Martin 1997;Taylor and Bradley 1997;Baddeley et al 1998;Brueckner and Zenou 2003;Bornhorst and Commander 2004;Novotný and Nosek 2012;Patuelli et al 2012;Huber 2013;López-Bazo and Motellón 2013;Zierahn 2013;Yang 2014;Zeilstra and Elhorst 2014;Granato et al 2015;Beyer and Stemmer 2016;Rios 2016). As Fischer and Nijkamp (2014, p. xxviii) argue, 'spatial interdependencies have always been at the heart of regional science research'.…”
Section: Economic Geography and Regional Studiesmentioning
confidence: 99%
“…These studies apply sophisticated non-spatial statistical analysis, including panel data model and regression analysis [26], logistic regression [27], logit models [28], gap decomposition for non-linear models [29], or stochastic kernel mapping [30].…”
Section: Introductionmentioning
confidence: 99%